Building a nation: The Jeroboams and the creation of two Israels - Davies, Philip R. (HTS teologiese studies, 2019)
This article represents a short reflective essay in honour of the Old Testament scholar Eben Scheffler. It focuses on the writing of the history of ancient Israel texts; examines different approaches to address the history of texts: minimalist and maximalist; and illustrates a minimalist approach in reference to the figure of the Israelite king Jeroboam II.